Legal Aspects of Genetically Modified Food Product Safety for Health in Indonesia - Abdullah Khamdi; Dian Anggraini Wikamorys; Waty Anton; Mokhamad Khoirul Huda (Institute of Medico-legal Publications Pvt Ltd, 2022)
Genetic Engineering is the transplantation of one gene to another, both between genes and across genes, toproduce valuable products for living beings. The rapid growth of genetic engineering in Indonesia and GeneticallyModified (GM) food products has raised many worries and issues about these foods posing a health risk whenconsumed. Concerns about GM food products are increasing, including the possibility of allergic reactions, genetransfer, and outcrossing. Indonesia is one of the countries that has accepted the Cartagena Protocol, a securityprotocol designed to protect biodiversity from the potential risk posed by genetically modified organisms createdby contemporary biotechnology. The writer, through this study, would like to convey the extent to which theexisting regulations in Indonesia regarding GM food product safety for public health and how the government’sresponsibility in GM food product safety is for public health. As a result of this study, GM food products had beenregulated by law, and the establishment of a Biosafety Commission was one form of government responsibility forpreserving the safety of GM food products for public health.